Anode electrode, preparation method of anode electrode, membrane electrode and application of membrane electrode
By introducing ionomers into the catalyst layer of the anode electrode to form a multi-layer structure, the problem of poor stability of the anode electrode is solved, and the effect of long-term stable operation and cost reduction is achieved.
Patent Information
- Application Number
- CN202411976011.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
In the prior art, the stability of the anode electrode is poor, and the catalyst layer is prone to fall off, which affects the performance of hydrogen production by solid polymer anionic electrolysis water.
By introducing ionomers into the catalyst layer of the anode electrode, a multi-layer structure is formed, which improves the water absorption capacity and shape stability of the electrode, and reduces the fall of the catalyst layer.
The long-term stable operation of the anode electrode is achieved, and it can operate stably for at least 40 hours at a current density of 1A·cm-2, which improves the durability of AEMWE and reduces costs.
Smart Images

Figure BDA0005222287140000091 
Figure BDA0005222287140000101 
Figure HDA0005222287470000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to an anode electrode, a preparation method thereof, a membrane electrode and applications thereof. Background Art
[0002] The solid polymer anion water electrolysis (AEMWE) hydrogen production technology combines the advantages of traditional alkaline liquid electrolyte water electrolysis and PEM water electrolysis. Non-precious metal catalysts such as Ni, Co, and Fe can be used in alkaline media, saving equipment and material costs under the premise of high-efficiency hydrogen production. The current performance problem restricting AEMWE is stability, of which the stability of the electrode accounts for a large part.
[0003] The preparation of electrodes by spraying is an important electrode preparation technology, which is widely used in the fields of fuel cells, capacitors and solar cells. It is a method of spraying liquid materials (such as coatings, catalyst inks, etc.) onto the surface of a substrate in a mist form through a spray gun or similar tool to form a desired coating or electrode. This method has the advantages of high preparation efficiency, high degree of automation, good coating uniformity, etc., and is particularly suitable for the preparation of electrodes with large areas and complex shapes. As an advanced spraying technology, ultrasonic spraying has the advantages of high coating uniformity, high raw material utilization, high coating thickness control accuracy and wide application range in electrode preparation. However, the electrodes prepared by the above-mentioned spraying method still have the problem of poor stability, and the catalyst layer is easy to fall off.
[0004] Therefore, it is of great significance to provide a method to improve the stability of AEMWE electrodes. Summary of the invention
[0005] The technical problem solved by the present invention is to provide an anode electrode. The anode electrode provided by the present application has good stability.
[0006] In view of this, the present application provides an anode electrode, which is composed of an anode electrode substrate, a catalyst layer formed on the surface of the anode electrode substrate, and an ionomer layer formed on the surface of the catalyst layer, and the raw materials of the catalyst layer include a non-precious metal catalyst, a solvent and an ionomer.
[0007] Preferably, in the catalyst layer, the ionomer includes one or more of polyterphenylfluorenylalkylene PFTA series compounds, Nafion and polybiphenylalkylene PBPA.
[0008] Preferably, in the catalyst layer, the ionomer is selected from Nafion, PFTA-75, a mixture of PFTA-75 and Nafion in a mass ratio of 1:(1-2), or a mixture of PBTA and Nafion in a mass ratio of 1:(1-2).
[0009] Preferably, in the catalyst layer, the ionomer is selected from a mixture of PFTA-75 and Nafion in a mass ratio of 1:(1-2) or a mixture of PBTA and Nafion in a mass ratio of 1:(1-2).
[0010] Preferably, in the catalyst layer, the solvent is selected from isopropanol and water, the mass ratio of the water to the isopropanol is 1:(3-10), and the non-precious metal catalyst includes NiFe2O4.
[0011] The present application also provides a method for preparing the anode electrode, comprising the following steps:
[0012] mixing a non-precious metal catalyst, a solvent and an ionomer to obtain a catalyst slurry;
[0013] mixing a solvent and an ionomer to obtain an ionomer slurry;
[0014] Forming the catalyst slurry on the surface of the anode electrode substrate and obtaining a catalyst layer after drying;
[0015] The ionomer slurry is formed on the surface of the catalyst layer, dried and then annealed to obtain an anode electrode.
[0016] Preferably, the solid content of the catalyst slurry is 1.0 to 10.0 wt %.
[0017] Preferably, the catalyst slurry is formed on the surface of the anode electrode substrate by spraying with a spray gun, and the loading amount of the non-precious metal catalyst in the catalyst layer is 1.0 to 5.0 mg / cm 2 .
[0018] The present application also provides a membrane electrode, comprising an anode electrode and a cathode electrode, wherein the anode electrode is the anode electrode described above or the anode electrode prepared by the preparation method described above.
[0019] The present application also provides the use of the membrane electrode in the electrolysis of water to produce hydrogen using solid polymer anions.
[0020] The present application provides an anode electrode, which is composed of an anode electrode substrate, a catalyst layer formed on the surface of the anode electrode substrate, and an ionomer layer formed on the surface of the catalyst layer, wherein the raw materials of the catalyst layer include a non-precious metal catalyst, a solvent and an ionomer; the present application introduces an ionomer into the catalyst layer of the anode electrode, which has good water absorption capacity and reduces the deformation of the anode electrode, thereby improving the stability of the anode electrode. At the same time, the anion groups in the ionomer can also form cross-links with metal ions, reducing the swelling of the ionomer and stabilizing the anode electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A schematic diagram of the process of preparing an anode electrode according to the present invention;
[0022] Figure 2 This is a stability test curve diagram of the membrane electrode prepared in Examples 1 to 4 of the present invention. DETAILED DESCRIPTION
[0023] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0024] In view of the problems of poor stability of anode electrodes and easy detachment of catalyst layers in the prior art, the present application provides an anode electrode, which achieves the stability of the anode electrode by introducing an ionomer into the catalyst layer, so that the obtained membrane electrode can operate stably for at least 40 hours during the electrolysis of water. Specifically, an embodiment of the present invention discloses an anode electrode, which is composed of an anode electrode substrate, a catalyst layer formed on the surface of the anode electrode substrate, and an ionomer layer formed on the surface of the catalyst layer, and the raw materials of the catalyst layer include a non-precious metal catalyst, a solvent, and an ionomer.
[0025] In the anode electrode provided in the present application, the anode electrode substrate is a substrate well known to those skilled in the art, and the present application does not impose any particular limitation on this. By way of example, the anode electrode substrate is nickel foam.
[0026] The raw materials of the catalyst layer include a non-precious metal catalyst, a solvent and an ionomer; wherein the non-precious metal catalyst is a catalyst well known to those skilled in the art, and in a specific embodiment, the non-precious metal catalyst is selected from NiFe2O4. In the present application, the solvent is selected from water and isopropyl alcohol (IPA); the mass ratio of the water to the isopropyl alcohol is 1:(3-10), and specifically, the mass ratio of the water to the isopropyl alcohol is 1:(4-6). The ionomer includes one or more of polyterphenylfluorenylalkylene PFTA series compounds, Nafion and polybiphenylalkylene PBPA; wherein the polyterphenylfluorenylalkylene PFTA series compounds are specifically selected from PFTA-75, and the polybiphenylalkylene PBPA is purchased from Jiamo Technology Co., Ltd. Specifically, the ionomer is selected from Nafion, PFTA-75, a mixture of PFTA-75 and Nafion in a mass ratio of 1:(1-2), or a mixture of PBTA and Nafion in a mass ratio of 1:(1-2); as a preferred embodiment, the ionomer is selected from a mixture of PFTA-75 and Nafion in a mass ratio of 1:(1-2), or a mixture of PBTA and Nafion in a mass ratio of 1:(1-2). In the catalyst layer, the mass ratio of the ionomer to the non-precious metal catalyst is 1:(5-10), and specifically, the mass ratio of the ionomer to the non-precious metal catalyst is 1:(7-9).
[0027] According to the present invention, an ionomer layer is also formed on the surface of the catalyst layer, and its raw materials include solvent and ionomer, and the solvent is specifically isopropanol and water; the volume ratio of the water to the isopropanol is 1: (3-10), and specifically, the mass ratio of the water to the isopropanol is 1: (4-6). The ionomer includes polyterphenylfluorenyl alkylene PFTA series compounds or polybiphenyl alkylene PBPA; the ratio of the water, isopropanol and the ionomer is 1ml: 4ml: (40-60) mg, and specifically, the ratio of the water, isopropanol and the ionomer is 1ml: 4ml: 50mg.
[0028] The present application also provides a method for preparing an anode electrode, and a specific process diagram is shown in FIG. Figure 1 As shown, the specific steps include:
[0029] mixing a non-precious metal catalyst, a solvent and an ionomer to obtain a catalyst slurry;
[0030] mixing a solvent and an ionomer to obtain an ionomer slurry;
[0031] Forming the catalyst slurry on the surface of the anode electrode substrate and obtaining a catalyst layer after drying;
[0032] The ionomer slurry is formed on the surface of the catalyst layer, dried and then annealed to obtain an anode electrode.
[0033] In the process of preparing the anode electrode, the present application first mixes the non-precious metal catalyst, the solvent and the ionomer to obtain a catalyst slurry; in this process, the mixing is preferably carried out by ultrasonic mixing to fully destroy the agglomerates of the non-precious metal particles and make the non-precious metal particles dispersed evenly, and the temperature of the ultrasound is 20 to 30°C. For the above raw materials, the ionomer is added in the form of an ionomer solution, the solvent in the ionomer solution is selected from dimethyl sulfoxide, and the concentration of the ionomer solution is 10 to 20wt%; more specifically, when the ionomer is selected from PFTA-75 or PBPA, the concentration of the ionomer solution is 10wt%, and when the ionomer is selected from Nafion, the concentration of the ionomer solution is 20wt%.
[0034] According to the present invention, an ionomer slurry is prepared, that is, a solvent and an ionomer are mixed to obtain the ionomer slurry.
[0035] The present application then prepares the obtained catalyst slurry on the surface of the anode electrode substrate, and obtains the catalyst layer after drying; in this process, the method of preparing the catalyst slurry on the surface of the anode electrode substrate can be specifically sprayed by a spray gun to achieve uniform distribution of the slurry on the electrode. The loading of the non-precious metal catalyst in the catalyst layer is 1.0 to 5.0 mg / cm 2 Specifically, the loading amount of the non-precious metal catalyst in the catalyst layer is 2.0 to 4.0 mg / cm 2 The drying method may be a baking method.
[0036] In the present application, the ionomer slurry is finally formed on the surface of the catalyst layer, dried and annealed; in this process, the method for preparing the ionomer slurry on the surface of the catalyst layer can adopt a method well known to those skilled in the art, for example, a coating method can be adopted. The ionomer loading in the ionomer layer is 0.1-1.0 mg / cm 2 Specifically, the ionomer loading in the ionomer layer is 0.35 to 0.45 mg / cm 2 The drying method may be a baking method, and the annealing treatment may be performed in a vacuum drying oven.
[0037] The present application also provides a membrane electrode, comprising an anode electrode and a cathode electrode, wherein the anode electrode is the anode electrode described in the above scheme.
[0038] In the membrane electrode, the cathode electrode is a cathode electrode well known to those skilled in the art. For example, the cathode electrode is an electrode having a cathode catalyst layer composited on the surface of carbon paper.
[0039] The present application also provides the use of the above membrane electrode in the production of hydrogen by electrolysis of water using solid polymer anions.
[0040] The present application provides an anode electrode, which reduces the deformation of the anode catalyst layer by introducing an ionomer into the catalyst layer, thereby improving the stability of the anode; under the working condition of anode water electrolysis, it has good stability (alkali resistance and high potential oxidation), and can be used at 1A·cm -2 Under the current density, it can run stably for at least 40 hours, which enhances the durability of AEMWE in terms of time dimension and reduces the cost of AEMWE.
[0041] In order to further understand the present invention, the anode electrode, the preparation method and the application thereof provided by the present invention are described in detail below in conjunction with the embodiments. The protection scope of the present invention is not limited by the following embodiments.
[0042] Example 1
[0043] Weigh 45.72 mg of NiFe2O4 in a bottle, add 0.91 ml of water and 3.66 ml of isopropanol (IPA), add 12.5 wt% of PFTA-75, control the temperature to be below 20°C for ultrasonication, mix thoroughly and take out to obtain a slurry with a solid content of 3.3%; add 2 ml of H2O and 8 ml of isopropanol to mix with 100 mg of PFTA-75 ionomer, perform ultrasonication below 20°C, mix thoroughly and take out to obtain an ionomer slurry; wherein 12.5 wt% = (the mass of PFTA-75 in a PFTA-75 solution with a concentration of 10 wt%) / (the mass of catalyst NiFe2O4 + the mass of PFTA-75 in a PFTA-75 solution with a concentration of 10 wt%) × 100%, and the solvent of the PFTA-75 solution with a concentration of 10 wt% is dimethyl sulfoxide;
[0044] Cut the gas diffusion layer into a suitable size, weigh it and fix it on the heating plate, adjust the temperature to 60℃; adjust the gas flow rate, pour the slurry into the spray gun, spray it slowly and evenly on the electrode to evaporate the solvent quickly; after the slurry is sprayed, take the electrode to the balance, weigh it and record it, and control the catalyst loading to 2mg / cm 2 ; The dried electrode is covered with a layer of 0.45 mg / cm formed by ionomer slurry 2 The PFTA-75 ionomer layer is dried and then placed in a vacuum drying oven for annealing to obtain an anode electrode; the anode electrode is sprayed on carbon paper with a loading of 1.0 mg / cm 2 The cathode catalyst layer and CO 15 The membrane was assembled into a membrane electrode; the device was installed to perform water electrolysis test, and the results are shown in Table 2.
[0045] Example 2
[0046] Weigh 45.72 mg of NiFe2O4 in a bottle, add 0.91 ml of water and 3.66 ml of IPA, add 12.5 wt% of a mixture of PFTA-75 and Nafion, control the temperature below 20 ° C for ultrasonication, mix thoroughly and take out to obtain a slurry with a solid content of 3.3%; add 2 ml of H2O and 8 ml of isopropanol and 100 mg of PFTA-75 ionomers are mixed, ultrasonicated at a temperature below 20° C., and taken out after being fully mixed to obtain ionomer slurry; wherein 12.5wt%=(total mass of PFTA-75 in 10wt% PFTA-75 solution+Nafion in 20wt% Nafion solution) / (mass of catalyst NiFe2O4+mass of PFTA-75 in 10wt% PFTA-75 solution+mass of Nafion in 20wt% Nafion solution)×100%, the solvent of 10wt% PFTA-75 solution is dimethyl sulfoxide; the mass ratio of PFTA-75 to Nafion is 1:1;
[0047] Cut the gas diffusion layer into a suitable size, weigh it and fix it on the heating plate, adjust the temperature to 60℃; adjust the gas flow rate, pour the slurry into the spray gun, spray it slowly and evenly on the electrode to evaporate the solvent quickly; after the slurry is sprayed, take the electrode to the balance, weigh it and record it, and control the catalyst loading to 2mg / cm 2 The dried electrode is covered with a layer of 0.45 mg / cm 2 The PFTA-75 ionomer layer is dried and then placed in a vacuum drying oven for annealing to obtain an anode electrode; the anode electrode is sprayed on carbon paper with a loading of 1.0 mg / cm 2 The cathode catalyst layer and CO 15 The membrane was assembled into a membrane electrode; the device was installed to perform water electrolysis test, and the results are shown in Table 2.
[0048] Example 3
[0049] Weigh 45.72 mg of NiFe2O4 in a bottle, add 0.91 ml of water and 3.66 ml of IPA, add 12.5 wt% of PFTA-75:Nafion=1:2, control the temperature below 20°C for ultrasonication, mix thoroughly and take out to obtain a slurry with a solid content of 3.3%; add 2 ml of H2O and 8 ml of isopropanol and 100 mg of PFTA-75 ionomers are mixed, ultrasonicated at a temperature below 20° C., and taken out after being fully mixed to obtain ionomer slurry; wherein 12.5wt%=(total mass of PFTA-75 in PFTA-75 solution with a concentration of 10wt%+Nafion in Nafion solution with a concentration of 20wt%) / (mass of catalyst NiFe2O4+mass of PFTA-75 in PFTA-75 solution with a concentration of 10wt%+mass of Nafion in Nafion solution with a concentration of 20wt%)×100%, the solvent of the PFTA-75 solution with a concentration of 10wt% is dimethyl sulfoxide; the mass ratio of PFTA-75 to Nafion is 1:2;
[0050] Cut the gas diffusion layer into a suitable size, weigh it and fix it on the heating plate, adjust the temperature to 60℃; adjust the gas flow rate, pour the slurry into the spray gun, spray it slowly and evenly on the electrode to evaporate the solvent quickly; after the slurry is sprayed, take the electrode to the balance, weigh it and record it, and control the catalyst loading to 2mg / cm 2 The dried electrode is covered with a layer of 0.45 mg / cm 2 The PFTA-75 ionomer layer is dried and then placed in a vacuum drying oven for annealing to obtain an anode electrode; the anode electrode is sprayed on carbon paper with a loading of 1.0 mg / cm 2 The cathode catalyst layer and CO 15 The membrane was assembled into a membrane electrode; the device was installed to perform water electrolysis test, and the results are shown in Table 2.
[0051] Example 4
[0052] Weigh 45.72 mg of NiFe2O4 in a bottle, add 0.91 ml of water and 3.66 ml of IPA, add 12.5 wt% of Nafion, control the temperature to be below 20°C for ultrasonication, mix thoroughly and take out to obtain a slurry with a solid content of 3.3%; add 2 ml of H2O and 8 ml of isopropanol and 100 mg of PFTA-75 ionomer, mix together, perform ultrasonication below 20°C, mix thoroughly and take out to obtain an ionomer slurry; wherein, 12.5 wt% = (mass of Nafion in Nafion solution with a concentration of 20 wt%) / (mass of catalyst NiFe2O4 + mass of Nafion in Nafion solution with a concentration of 20 wt%) × 100%;
[0053] Cut the gas diffusion layer into a suitable size, weigh it and fix it on the heating plate, adjust the temperature to 60℃; adjust the gas flow rate, pour the slurry into the spray gun, spray it slowly and evenly on the electrode to evaporate the solvent quickly; after the slurry is sprayed, take the electrode to the balance, weigh it and record it, and control the catalyst loading to 2mg / cm 2 The dried electrode is covered with a layer of 0.45 mg / cm 2 The PFTA-75 ionomer layer is dried; then placed in a vacuum drying oven for annealing to obtain an anode electrode; sprayed on carbon paper with a loading of 1.0 mg / cm 2 The cathode catalyst layer and CO 15 The membrane was assembled into a membrane electrode; the device was installed to perform water electrolysis test, and the results are shown in Table 2.
[0054] Example 5
[0055] Weigh 45.72 mg of NiFe2O4 in a bottle, add 0.91 ml of water and 3.66 ml of IPA, add 12.5 wt% of PBPA: Nafion = 1:1, control the temperature to be below 20°C for ultrasonication, mix thoroughly and take out to obtain a slurry with a solid content of 3.3%; add 2 ml of H2O and 8 ml of isopropanol and mix with 100 mg of PBPA ionomer, mix thoroughly and take out to obtain an ionomer slurry; wherein 12.5 wt% = (total mass of PBPA in 10 wt% PBPA solution + Nafion in 20 wt% Nafion solution) / (mass of catalyst NiFe2O4 + mass of PBPA in 10 wt% PBPA solution + mass of Nafion in 20 wt% Nafion solution) × 100%, the solvent of the 10 wt% PBPA solution is dimethyl sulfoxide; the mass ratio of PBPA to Nafion is 1:1;
[0056] Cut the gas diffusion layer into a suitable size, weigh it and fix it on the heating plate, adjust the temperature to 60℃; adjust the gas flow rate, pour the slurry into the spray gun, spray it slowly and evenly on the electrode to evaporate the solvent quickly; after the slurry is sprayed, take the electrode to the balance, weigh it and record it, and control the catalyst loading to 2mg / cm 2 The dried electrode is covered with a layer of 0.45 mg / cm 2 The PBPA ionomer layer was dried and then annealed in a vacuum drying oven to obtain an anode electrode; the anode electrode was sprayed on carbon paper with a loading of 1.0 mg / cm 2 The cathode catalyst layer and CO 15The membrane was assembled into a membrane electrode; the device was installed to perform water electrolysis test, and the results are shown in Table 2.
[0057] Example 6
[0058] Weigh 45.72 mg of NiFe2O4 in a bottle, add 0.91 ml of water and 3.66 ml of IPA, add 12.5 wt% of PBPA: Nafion = 1:2, control the temperature to be below 20°C for ultrasonication, mix thoroughly and take out to obtain a slurry with a solid content of 3.3%; add 2 ml of H2O and 8 ml of isopropanol to mix with 100 mg of PBPA ionomer, perform ultrasonication below 20°C, mix thoroughly and take out to obtain an ionomer slurry; wherein, 12.5 wt% = (total mass of PBPA in 10 wt% PBPA solution + Nafion in 20 wt% Nafion solution) / (mass of catalyst NiFe2O4 + mass of PBPA in 10 wt% PBPA solution + mass of Nafion in 20 wt% Nafion solution) × 100%, the solvent of the 10 wt% PBPA solution is dimethyl sulfoxide; the mass ratio of PBPA to Nafion is 1:2;
[0059] Cut the gas diffusion layer into a suitable size, weigh it and fix it on the heating plate, adjust the temperature to 60℃; adjust the gas flow rate, pour the slurry into the spray gun, spray it slowly and evenly on the electrode to evaporate the solvent quickly; after the slurry is sprayed, take the electrode to the balance, weigh it and record it, and control the catalyst loading to 2mg / cm 2 The dried electrode is covered with a layer of 0.45 mg / cm 2 The PBPA ionomer layer was dried and then placed in a vacuum drying oven for annealing. The loading amount was sprayed on carbon paper at 1.0 mg / cm 2 The cathode catalyst layer and CO 15 membrane, assembled into membrane electrode; installed with devices for water electrolysis (1MKOH, 80℃, 1A / cm 2 The test was run under ), and the results are shown in Table 2.
[0060] Table 1 Example and comparative example formula table
[0061]
[0062] Table 2 Performance data of membrane electrode prepared in Example
[0063]
[0064]
[0065] Figure 2 The data graph of the voltage variation over time of the membrane electrodes prepared in Examples 1 to 4 during the water electrolysis process for at least 40 hours shows that with the increase of the Nafion ionomer content, the stability of the battery voltage becomes better and better. However, since Nafion cannot conduct OH-, it is preferred to select the condition of PFTA-75:Nafion=1:1~1:2. Other AEIs also have this effect, such as PBPA.
[0066] After the membrane electrodes prepared in Examples 1 to 4 reacted for 45 hours, the detached catalyst in the electrolyte was dissolved with hydrochloric acid and diluted to between 0.1 and 1.0 mg / L, shaken well, and 15 ml of liquid was extracted. The catalyst content in the liquid was tested using an inductively coupled plasma emission spectrometer electrode, and the total catalyst mass was calculated. The amount of detached catalyst is shown in Table 3:
[0067] Table 3 Catalyst shedding data of membrane electrode prepared in Example
[0068] Ionomer Mass of catalyst falling off (mg) PFTA-75 0.9083 PFTA-75:Nafion=2:1 0.2046 PFTA-75:Nafion=1:1 0.1957 Nafion 0.1587
[0069] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0070] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An anode electrode, comprising an anode electrode substrate, a catalyst layer formed on the surface of the anode electrode substrate, and an ionomer layer formed on the surface of the catalyst layer, wherein the raw materials of the catalyst layer include a non-precious metal catalyst, a solvent and an ionomer.
2. The anode electrode according to claim 1, characterized in that: In the catalyst layer, the ionomer includes one or more of polyterphenylfluorenylalkylene PFTA series compounds, Nafion and polybiphenylalkylene PBPA.
3. The anode electrode according to claim 1 or 2, characterized in that: In the catalyst layer, the ionomer is selected from Nafion, PFTA-75, a mixture of PFTA-75 and Nafion in a mass ratio of 1:(1-2), or a mixture of PBTA and Nafion in a mass ratio of 1:(1-2).
4. The anode electrode according to claim 3, characterized in that: In the catalyst layer, the ionomer is selected from a mixture of PFTA-75 and Nafion in a mass ratio of 1:(1-2) or a mixture of PBTA and Nafion in a mass ratio of 1:(1-2).
5. The anode electrode according to claim 1, characterized in that: In the catalyst layer, the solvent is selected from isopropanol and water, the mass ratio of the water to the isopropanol is 1:(3-10), and the non-precious metal catalyst includes NiFe2O4.
6. The method for preparing the anode electrode according to claim 1, comprising the following steps: mixing a non-precious metal catalyst, a solvent and an ionomer to obtain a catalyst slurry; mixing a solvent and an ionomer to obtain an ionomer slurry; Forming the catalyst slurry on the surface of the anode electrode substrate and drying to obtain a catalyst layer; The ionomer slurry is formed on the surface of the catalyst layer, dried and then annealed to obtain an anode electrode.
7. The preparation method according to claim 6, characterized in that: The solid content of the catalyst slurry is 1.0-10.0 wt%.
8. The preparation method according to claim 6, characterized in that: The catalyst slurry is formed on the surface of the anode electrode substrate by spraying with a spray gun, and the loading amount of the non-precious metal catalyst in the catalyst layer is 1.0 to 5.0 mg / cm 2 .
9. A membrane electrode, comprising an anode electrode and a cathode electrode, characterized in that: The anode electrode is the anode electrode according to any one of claims 1 to 5 or the anode electrode prepared by the preparation method according to any one of claims 6 to 8.
10. Use of the membrane electrode according to claim 9 in the production of hydrogen by electrolysis of water using solid polymer anions.
Citation Information
Patent Citations
PEM water electrolysis membrane electrode as well as preparation method and application thereof
CN113604817A
Preparation of integrated membrane electrode capable of reducing interface impedance
CN114597460A
Preparation method of membrane electrode and membrane electrode
CN115863715A
Electrolytic water membrane electrode and preparation method thereof
CN116555803A
Composite catalyst, composite catalyst coating film, preparation method of composite catalyst coating film and water electrolysis hydrogen production equipment
CN116905029A